Activation of O2 over three-dimensional manganese oxide nanoprisms under ambient conditions towards oxidative removal of aqueous organics. Issue 4 (18th March 2022) - Hao, Zixuan; Bi, Xiuru; Wang, Xiaopei; Liu, Xiang; Meng, Xu
Abstract : A three-dimensional OMS-2 catalyst was synthesized via a bimetallic-doping strategy and O2 could be activated over it under ambient conditions for oxidative degradation of aqueous organics. Abstract : Three-dimensional nanomaterials are generally beneficial to catalytic performance because of their larger specific surface area, more exposed active sites, enhanced mass transfer and shorter diffusion distance between reactants and catalysts. In this study, a bimetallic doping strategy was developed for the synthesis of three-dimensional α-phase manganese oxide (Ce–Bi-OMS-2) with nanoprism structural morphology for the first time. The doping component and dosage both affected the size, morphology, crystal phase and textural properties of Ce–Bi-OMS-2. The 3D material could efficiently activate O2 under ambient conditions and further be used as the catalyst to degrade bisphenol A at 66.8% degradation rate with a rate constant of 0.0179 min −1 under standard conditions. Moreover, a degradation rate of 99% and mineralization rate of 67% for bisphenol A were realized under optimal conditions. XPS, radical quenching experiments and EPR suggested that O2 ˙ − was mainly responsible for the degradation, and ˙OH and 1 O2 played secondary dominant roles. Further investigations indicated that structural dimension, enhanced specific surface area (147 m 2 g −1 ) and rich surface oxygen vacancies contributed to the good catalytic performance. This work not only provides a novel and facile doping strategy for the construction of a 3D nanostructured material but also demonstrates the activation of O2 over a 3D catalyst for the degradation of aqueous organic pollutants.